Relationship between Body Schema and Scholar Maturity: A Study from the National College of Banat in Timisoara, Romania - Mariana Cristina Șunei; Simona Petracovschi; Eugen Bota; Bogdan Almajan-Guță; Adrian Nagel (MDPI AG, 2022)
The purpose of this study is to analyze the role and importance of specific physical exercises in the development of the body schema in preparatory class pupils and its effect on the development of maturity. Methods: The experiment took place over a period of 10 weeks in which two physical education lessons per week were scheduled; the lessons include specific themes for the development of the body schema and contain exercises to arouse pupils' interest in sports and physical activities from this age. A number of 150 pupils aged between 5 years and 6 months and 7 years and 6 months participated in the experiment. The pupils were divided into two groups: the experimental group (76 pupils, 32 boys and 34 girls) and the control group (74 pupils, 31 boys and 33 girls). Next, the "Draw-a-Person" Test was applied at the beginning and end of the experiment. Results: The analysis of the results highlights the fact that after completing the intervention plan there is a significant improvement in the results of the experimental group on the Maturity Scale and implicitly on the three development scales: Head Scale, Body Schema Scale, and Clothing Scale. Among the three scales, the Body Schema Scale has the greatest influence on the Maturity Scale (r = 0.841). Conclusions: The preparatory class produces a connection between the kindergarten and the school; furthermore, the physical education lessons with an emphasis on the development of the body scheme contribute to the development of maturity and school preparation of the pupils.